ICESat-2 for Canopy Cover Estimation at Large-Scale on a Cloud-Based Platform - Akturk, Emre; Popescu, Sorin C.; Malambo, Lonesome (MDPI AG, 2023)
Forest canopy cover is an essential biophysical parameter of ecological significance, especially for characterizing woodlands and forests. This research focused on using data from the ICESat-2/ATLAS spaceborne lidar sensor, a photon-counting altimetry system, to map the forest canopy cover over a large country extent. The study proposed a novel approach to compute categorized canopy cover using photon-counting data and available ancillary Landsat images to build the canopy cover model. In addition, this research tested a cloud-mapping platform, the Google Earth Engine (GEE), as an example of a large-scale study. The canopy cover map of the Republic of Türkiye produced from this study has an average accuracy of over 70%. Even though the results were promising, it has been determined that the issues caused by the auxiliary data negatively affect the overall success. Moreover, while GEE offered many benefits, such as user-friendliness and convenience, it had processing limits that posed challenges for large-scale studies. Using weak or strong beams’ segments separately did not show a significant difference in estimating canopy cover. Briefly, this study demonstrates the potential of using photon-counting data and GEE for mapping forest canopy cover at a large scale.
Keywords: ATL08; Chemical technology; canopy cover estimation; canopy cover estimation; ICESat-2; ATL08; photon counting lidar; Landsat; Google Earth Engine; photon counting lidar; TP1-1185; Google Earth Engine; Landsat; Article; ICESat-2; 13. Climate action; 15. Life on land